Vírus da artrite encefalite caprina: isolamento e caracterização parcial do gene gag. - Patricia Pinto de Lima (2002)
In this study, a commercial dairy goat herd located in the state of Minas Gerais was tested for the presence of infection by caprine arthritis encephalitis (CAEV), by testing Immunodiffusion Agarose gel (AGID). Blood samples from 12 seropositive animals, exhibiting no clinical signs of infection by CAEV were collected for viral isolation. For this purpose, monocyte-derived macrophages were co-cultured with goat synovial membrane cells (MSC), resulting in the achievement of the isolates that showed cytopathic effects of the persistent type, similar to that observed for CAEV. A PCR was designed to amplify part of the gag gene of proviral genome coding for the viral capsid protein (p25). All five isolates were amplified by PCR and that three of these, called named BR-UFMG/PL1, BR-UFMG/PL2 BR-UFMG/PL3 and were sequenced directly from their PCR products. The alignment of multiple sequences with sequence of other small ruminants lentiviruses (SRLV) and the dendrogram obtained from GenBank revealed that these new isolates of CAEV are unique and distinct from other samples SRLV, with higher nucleotide and amino acid identity among themselves and with to CAEV than to the Maedi-Visna virus (MVV)